What are the Leading Sectors Expected to Reduce Inequality in South Sumatra Province? - Dian Apriyani (Department of Development Economics, Universitas Sriwijaya, 2021)
This study aims to find out the leading sectors and to analyze income inequality in South Sumatera Province, which the result is very important since no recent research has been done in this field for the study area. The data used in this study are secondary data from 2011-2020 which are sourced from the publications of the BPS-Statistic of South Sumatera Province. To find out inequality and investigate its causes, Klassen typological analysis, Williamson index, and Theil's entropy index are used. Meanwhile, to analyze the potential leading sectors, a combination of Location Quotient analysis, Shift Share Analysis, and sectoral typology is used. The results of this study suggest that local governments develop the agricultural sector because it is proven to have excellent potential as a leading sector. In addition, the trade, hotel, and restaurant sector is a special sector and good to be developed because eleven regencies/cities have high potency for this sector. The results of the study also show that the regencies/cities in South Sumatera Province are grouped in quadrant III of Klassen’s, which is a relatively underdeveloped area. Income inequality in South Sumatra Province is categorized high with a Williamson index of 0.71, with the cause of the inequality being the inequality between groups of regencies/cities producing oil and gas.